Perceived professional benefits and associated factors among nurses during the COVID‐19 pandemic: A cross‐sectional study - Xiaomin Wang; Feifei Chen; Pengfei Dai; Xingfeng Lin; Lei Qi (Nursing Open, 2023)
Abstract Aims To examine the perceived professional benefits (PPB) and associated factors among nurses during the coronavirus disease 2019 (COVID‐19) pandemic in China. Design Cross‐sectional study. Methods Using the snowball sampling method, 492 nurses (478 females, 14 males) were recruited. Data were collected using an online survey, including participants' socio‐demographic and working characteristics, psychological distress related to the COVID‐19 pandemic, dealing with professional frustration, professional self‐reflection and PPB from 1–30 April 2020. Results Nurses experienced high levels of PPB. In linear regression analysis, self‐perceived concerns about COVID‐19, emotional shock caused by it, risk perception towards their occupations, dealing with professional frustration and professional self‐reflection were positively associated with PPB among nurses. These factors explained 84% variance in PPB. Conclusions This study highlighted that although the nurses experienced psychological distress, they gained high PPB during the COVID‐19 pandemic. Additionally, to facilitate nurses' efforts to achieve professional growth, more educational resources and opportunities for engaging in reflective practices could be provided.